5 - Les effets de l'aide bilatérale et multilatérale sur l'agriculture africaine: L'exemple du Sénégal: by Mamadou Dansokho - Mamadou Dansokho, (Africa Development, 1992)
The major determinant of the economic crisis in Senegal is the poor performance of the agricultural sector. In the 80s Senegal adopted a new agricultural policy (NAP) which was designed to reflect and accommodate the various conditionalities by the World Bank and the IMF. The main features of NAP includes: the reduction of the role of par astotais in agriculture , the formulation of a coherent policy on prices , the privatization of the distribution of agricultural inputs , the restoration of bank liquidity , the amelioration of fiscal performance and the allocation of resources to the productive sectors. These measures triggered an increase in the price of basic foodstuffs and petroleum products; an increase in taxes and fertilizer prices ; the rebate to peasant producers and a reduction of operating costs and of equipment. Another interesting feature that accompanied these conditionalities was the formation of a coherent froiiï by donors under the auspices of the World Bank. The case of Senegal confirms the hypothesis that external assistance is a mechanism that principally benefits the donor country through the sale of industrial goods and service and the strengthening of their commercial shipping lines. For the recipient country food aid tends to slow down production and consumption of local cereals and sustains a price structure that favours imported cereals.